Aplicación móvil para las rutas de evacuación en caso de erupción del volcán Cotopaxi. - Atupaña Arias, Jorge Luis (2019)
From the reactivation given on August 14, 2015 in the Cotopaxi volcano, there was been looked a information about a contingency plan within the canton population Latacunga. Before this event, the population was forced of evacuating to safe places and was looked the disowning of evacuation routes and safe shelters. The question that should was been or should will be asked is: Where should we go and how should we act? For this reason has been proposed to use hybrid technology for the development of a mobile application with management of its content on a web platform, through a web-service and so centralize, disseminate information about the contingency plan in front of a possible eruption of the Cotopaxi volcano in the Latacunga canton. For the construction of this hybrid system was used the Mobile-D methodology (mobile application) and the incremental Iterative model (web application). Through these work environments are specified the following modules for getting the expected results: A) Secure route module to a nearest shelter, since it, the user visualizes the hostel closest his current position. B) Module hostels and their parishes, in this way, the user selects a parish to visualize their hostels and the administrator manages this information, until this moment are centralized 131 shelters, which are located in t he Latacunga canton. C) State monitoring module on the Cotopaxi volcano, since this the user visualizes the volcano state, by means of 4 monitoring cameras that are located at strategic points. D) Module of record and search from missing people, through this module, the user records, searches for people and the administrator manages the information that was registered by the users. E) Information module about the contingency plan, in that the user visualizes relevant information about how to act, the emergency kit and alert levels. F) Communication module with aid agencies, on this the user will have a communication with different aid agencies within the canton Latacunga. G) Module of online and offline application, finally, the user can interact with the mobile application, regularly, with access to the Internet. Otherwise, users can see the necessary information without access to the Internet.